Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>2</mn></mrow></mfrac><mo>⋅</mo><mrow><mo>(</mo><mi>h</mi><mrow><mo>(</mo><mi>c</mi><mo>+</mo><mi>d</mi><mo>)</mo></mrow><mo>)</mo></mrow><mo>=</mo><mi>A</mi></mstyle></math> .

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mi>h</mi><mrow><mo>(</mo><mi>c</mi><mo>+</mo><mi>d</mi><mo>)</mo></mrow></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Apply the distributive property.

Subtract <math><mstyle displaystyle="true"><mi>h</mi><mi>c</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mi>h</mi><mi>d</mi><mo>=</mo><mn>2</mn><mi>A</mi><mo>-</mo><mi>h</mi><mi>c</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>d</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify each term.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn><mi>c</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Rewrite <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn><mi>c</mi></mstyle></math> as <math><mstyle displaystyle="true"><mo>-</mo><mi>c</mi></mstyle></math> .

Do you know how to Solve for d A=1/2h(c+d)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.